2017
DOI: 10.1016/j.riam.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the infection process by Lecanicillium fungicola in Agaricus bisporus by scanning electron microscopy

Abstract: Scanning electron microscopy enabled the process of colonization and reproduction to be observed within the formation of phialides, conidiophores and verticils of L. fungicola. The formation of calcium oxalate crystals by the pathogen was also visible using the X-ray microanalysis, both at the hyphae in the Petri plate and at basidiocarp infection site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Conidia were obclavate, had 3 or more spiral phialides, and were in imbricate chains with short imbricate chains on erected conidiophores ( Figure 3 ). The morphological features of RV26 resembled Simpliciium obclavatum ( Santana et al, 2017 ).…”
Section: Resultsmentioning
confidence: 98%
“…Conidia were obclavate, had 3 or more spiral phialides, and were in imbricate chains with short imbricate chains on erected conidiophores ( Figure 3 ). The morphological features of RV26 resembled Simpliciium obclavatum ( Santana et al, 2017 ).…”
Section: Resultsmentioning
confidence: 98%
“…This study evaluated the electron microscopic changes in the lice exposed to permethrin and 6-paradol according to the protocol described by Nunes et al . [ 30 ]. Briefly, the phases of the process are as follows: The lice were pre-fixed in 2.5% glutaraldehyde at 4°C for 6 h and then fixed in 1% osmium tetroxide for 2 h and rinsed in 0.1-M phosphate buffer (pH 7.2).…”
Section: Methodsmentioning
confidence: 99%
“…For observation by SEM, the samples (0.5 cm in length) after being infected for 3 d were processed following the method of Nunes et al [13] with modifications. The samples were fixed in 2.5% glutaraldehyde in 0.05 M phosphate buffered saline (pH 7.2) for 8 h at 4 • C, and then washed with deionized water for 7 min.…”
Section: Transformation Of Rfp-tagged Calcarisporium Cordycipiticola and Microscopymentioning
confidence: 99%
“…With electron microscopy and cytohistological techniques, Zhou found that H. perniciosus infected A. bisporus through the secretion of cell wall degradation enzymes and mechanical pressure from the appressorium [12]. L. fungicola did not produce a specialized structure, however, spores and hyphae of L. fungicola adhered to the surface of the host A. bisporus, and then protruded into the hyphae of the host [13]. Whether C. cordycipiticola can produce the specialized structure during infection, and how it interacted with the host C. militaris are our major concerns.…”
Section: Introductionmentioning
confidence: 99%